Chiral phonons and giant magneto-optical effect in CrBr₃ 2D magnet - Yin, Tingting (2021)
Phonons with chirality determine the optical helicity of inelastic light scattering processes due to their nonzero angular momentum. Here it is shown that 2D magnetic CrBr3 hosts chiral phonons at the Brillouin-zone center. These chiral phonons are linear combinations of the doubly-degenerate Eg phonons, and the phonon eigenmodes exhibit clockwise and counterclockwise rotational vibrations corresponding to angular momenta of l = ± 1. Such Eg chiral phonons completely switch the polarization of incident circularly polarized light. On the other hand, the non-degenerate non-chiral Ag phonons display a giant magneto-optical effect under an external out-of-plane magnetic field, rotating the plane of polarization of the scattered linearly polarized light. The corresponding degree of polarization of the scattered light changes from 91% to -68% as the magnetic field strength increases from 0 to 5 T. In contrast, the chiral Eg modes display no field dependence. The results lay a foundation for the study of phonon chirality and magneto-optical phenomena in 2D magnetic materials, as well as their related applications, such as the phonon Hall effect, topological photonics, and Raman lasing.